Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1460-9568.1989.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Eye Movements and Gaze Holding in the Head‐Restrained Pigmented Rat

Abstract: Spontaneous saccadic eye movements were recorded in seven head-restrained pigmented rats by means of a phase detection search coil system, both in the light and in the dark. In an illuminated environment, all the rats made numerous spontaneous saccades with an average amplitude of 13.2 deg (+/- 2.2 SD) and a maximal amplitude of 35 deg. In the dark, mean saccadic amplitude was significantly reduced to 9.2 deg (+/- 2.0 SD). Saccadic peak velocity increased linearly as a function of saccadic size, with no satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
4
24
0
Order By: Relevance
“…In particular, the characteristics of eye movements in typical traces turned out to be very similar to previously published findings (Chelazzi et al 1989;Niell and Stryker 2010;Zoccolan et al 2010). For most of the time (75%), eye position was at one particular central position (within 1.25°from the median X and Y position for the whole trace).…”
Section: Control Of Retinal Stimulationsupporting
confidence: 68%
“…In particular, the characteristics of eye movements in typical traces turned out to be very similar to previously published findings (Chelazzi et al 1989;Niell and Stryker 2010;Zoccolan et al 2010). For most of the time (75%), eye position was at one particular central position (within 1.25°from the median X and Y position for the whole trace).…”
Section: Control Of Retinal Stimulationsupporting
confidence: 68%
“…It has been reported that the time constant of a centripetal drift after an eye movement to an eccentric direction (i.e., the time constant for the neural integrator) is Ͼ20 s in the cat (Robinson, 1974), monkey (Cannon and Robinson, 1987), and human (Becker and Klein, 1973). Although the time constant in the rodent (Ϸ2 s) [rat (Chelazzi et al, 1989); mouse (van Alphen et al, 2001)] is shorter than that in the cat and primates, it is longer than the duration of the EPSC responses observed in the present study. Therefore, the local PHN network alone is unlikely to be sufficient to explain the mechanism of gaze holding.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to consider whether the differences between rodent and primate vision could help to explain the apparent disparity between encoding of head orientation in rodent EC and encoding of eye movements in primate EC. The primate visual system is distinctly different from the visual system of common laboratory rodents, which have a larger field of view, make few saccades, and lack a specialized retinal region like the primate fovea (29)(30)(31)(32). Consequently, sampling by moving the visual field via head movements in rodents might be similar to moving the fovea with the eyes in primates.…”
Section: Discussionmentioning
confidence: 99%